Psihološki dejavniki v poklicni rehabilitaciji oseb po nezgodni možganski poškodbi - Jakopec, Zlatka (Rehabilitacija (Ljubljana), 2010)
Employment outcome following traumatic brain injury is the result of a complex interaction between injury factors, social and environmental circumstances, pre-morbid personality and the individual's psychological reactions to all of the above. Beside injury severity and post-injury impairments, another important factor is the subjective, psychological impact of the injury to each individual in relation to his/her personality, adjustment abilities and coping strategies, self-appraisal and the emotional reactions to the decrease of abilities and perspectives. The paper describes some psychological factors that moderate return-to-work outcome following traumatic brain injury and therefore require appropriate attention in vocational rehabilitation programs. Basic guidelines for psychological treatment and vocational rehabilitation following traumatic brain injury are presented that appear to be effective in other countries and should therefore be developed in Slovenia.
Keywords: kognitivne spremembe; možganske poškodbe; psihološki dejavniki; rehabilitacija; vocational rehabilitation